Budaya Arsitektur Gapura Kayangan Api sebagai Representasi Etnomatematika dalam Pola Barisan Aritmatika - Yuni Arifatur Rohmah; Marhayati; Elly Susanti (CV MUARA EDUKASI, 2025)
This study aims to explore the concept of arithmetic sequences contained in the architectural structure of the gates in the Kayangan Api tourist area, Bojonegoro, through an ethnomathematics approach. The Kayangan Api gates not only function as traditional architectural elements, but also contain mathematical patterns that can be analyzed formally. The type of research used is qualitative with an ethnographic approach, through field observations, interviews, documentation, and literature reviews. The results show that the arrangement of the gates in Kayangan Api represents arithmetic sequence and sequence patterns, both in terms of size, height, and distance between structures. This pattern reflects the existence of mathematical regularity in traditional architectural works built with cultural values ​​and spiritual symbolism. These findings strengthen the view that ethnomathematics can be a bridge between local cultural heritage and formal mathematical concepts, and can be used as a context for more meaningful mathematics learning in schools.